Meningkatkan Kompetensi dengan Penggunaan Modul Paket Keahlian Produktif - Riana T. Mangesa; M. Yusuf Mappiasse (Seminar Nasional LP2M UNM, 2019)
Abstract. The efforts to improve student learning outcomes can be done by providing quality learning resources in the form of appropriate and quality module-based teaching materials to improve the individual abilities of students and teacher professional competence. Module development is based on the main reason that the availability of quality teaching materials is considered the most urgent matter compared to other efforts. Module development is based on the main reason that the availability of quality teaching materials is considered the most urgent matter compared to other efforts.This type of research is Research and Development (R&D) research to produce Module-based teaching materials on subjects analyzing electrical circuits to improve learners' abilities. The development model used in this study is the four-D model (Thiagarajan and Dorothy S. Semmel dan Melvyn I. Semmel, 1974) with stages; Define, Design, Develop and Disseminate, so that practical and effective products are obtained Keywords: Modules, Learning Outcomes, Vocational School